A Transdisciplinary Perspective on Hedonomic Sustainability Design. (April 2014) - Fiore, Stephen M.; Phillips, Elizabeth; Sellers, Brittany C.
The impact of climate change should be a key concern of those in the human factors/ergonomics (HF/E) discipline. Our specialized knowledge and expertise can be applied toward mitigating the effects of climate change. In this article, we unite two perspectives to illustrate how HF/E can more productively contribute to the research and practice of sustainability. First, we describe differing forms of cross-disciplinary research, with a particular focus on the notion of transdisciplinary research and the concept of hedonomic design. Second, we unite these ideas to illustrate how they provide a set of complementary concepts that can guide HF/E sustainability research.